Does the Financial Development Spur Export Performance? Evidence from Turkish Firm-Level Data - Serap Coban (International Journal of Economics and Financial Issues, 2015)
This paper investigates the causal relationship between financial development and export performance of firms in manufacturing sector in Turkey over the 1991-2012 period. After constructing banking sector and stock market financial development indexes and grouping the firms according to financial constraint indicators, for each groups and all of the firms in the sample panel causality test conducted developed by Dumitrescu and Hurlin (2012). The empirical evidence shows while development of the stock market plays a supportive role in increasing export performance for all groups, the direction of causality between development of banking sector and export performance can differ according to groups. The empirical evidence demonstrates the importance of policy reforms in the financial sector for the international trade. The financial development can be used as a predictor of export performance.